PENGARUH STRUKTUR MODAL, RETURN ON EQUITY DAN FIRM SIZE TERHADAP PRICE TO BOOK VALUE PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - SILALAHI, ESLI; SINAGA, RIA VERONICA; SIMBOLON, JUWITA; SIHOTANG, HELENA (UNIKA Santo Thomas, 2022)
This study aims to determine and explain the effect of Capital Structure, Return On Equity, and Firm Size partially and significantly or simultaneously and significantly on Price to Book Value in property and real estate companies listed on the Indonesia Stock Exchange. The population of this research is property and real estate companies listed on the Indonesia Stock Exchange which consist of 60 companies. The sample selection was done by purposive sampling method that is based on the research objectives with several criteria. The number of samples in this study were 20 companies. The data used is secondary data originating from the company's financial statements which can be accessed through the Indonesia Stock Exchange website (www.idx.co.id). The data analysis technique used is multiple linear regression analysis by testing the classical assumptions first, then performing the t test and F test with a significance level of 5%. The results of the t test show that Capital Structure has a negative and significant effect on Price to Book Value, while Return On Equity and Firm Size have a positive and significant effect on Price to Book Value. The results of the F test show that Capital Structure, Return On Equity, and Firm Size have a simultaneous and significant effect on Price to Book Value.